Differential effects of vildagliptin and glimepiride on glucose fluctuations in patients with type 2 diabetes mellitus assessed using continuous glucose monitoring. Issue 12 (14th July 2013) - He, Y. L.; Foteinos, G.; Neelakantham, S.; Mattapalli, D.; Kulmatycki, K.; Forst, T.; Taylor, A.
Abstract : Aim: To assess whether there is a difference in the effects of vildagliptin and glimepiride on glucose fluctuation in patients with type 2 diabetes mellitus (T2DM) using continuous glucose monitoring (CGM). Methods: This was an open‐label, randomized cross‐over study conducted in T2DM patients. A total of 24 patients (age: 58.3 ± 5.56 years, baseline HbA1c: 7.6 ± 0.50%) who were on stable metformin monotherapy (500–3000 mg) were enrolled, and all completed the study. Each patient received two 5‐day treatments (vildagliptin 50 mg b.i.d. or glimepiride 2 mg q.d.) in a cross‐over manner. Various biomarkers and blood glucose concentrations were measured following breakfast. The 24‐h glucose profiles were also measured using the CGM device at baseline and after 5 days of treatment, and fluctuations in glucose levels were estimated from CGM data. Results: Both vildagliptin and glimepiride reduced postprandial glucose levels, based on both CGM data (15% vs. 16%) and measured plasma glucose (13% vs.17%). Vildagliptin showed lower glucose fluctuations than glimepiride as measured by mean amplitude of glycaemic excursions (MAGE, p = 0.1076), standard deviation (s.d., p = 0.1346) of blood glucose rate of change, but did not reach statistical significance attributed to the small sample size. MAGE was reduced by ∼20% with vildagliptin versus glimepiride. Vildagliptin led to statistically significant lowering of the rate of change in the median curve (RCMC) and interquartile range (IQR) of glucose. Treatment with vildagliptin significantly increased the levels of active glucagon‐like peptide‐1 by 2.36‐fold (p ≤ 0.0001) and suppressed glucagon by 8% (p = 0.01), whereas glimepiride significantly increased the levels of insulin and C‐peptide by 21% (p = 0.012) and 12% (p = 0.003), respectively. Conclusions: Vildagliptin treatment was associated with less fluctuation of glucose levels than glimepiride treatment as assessed by 24‐h CGM device, suggesting vildagliptin may have the potential to offer long‐term beneficial effects for patients with T2DM in preventing the development of complications of diabetes.